2013
DOI: 10.1088/1751-8113/46/30/305202
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries of charged particle motion under time-independent electromagnetic fields

Abstract: A symmetry analysis is presented for the three-dimensional nonrelativistic motion of charged particles in arbitrary stationary electromagnetic fields. The general form of the Lie point symmetries is found along with the fields that respect them, considering non-trivial cases of physical interest. The restrictions placed upon the electromagnetic field yield five classes of solutions, expressed in terms of the vector and scalar potentials. The Noether type symmetries are also investigated and their corresponding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…The reduction process is the main application of Lie symmetries, however, it is not a univocal approach. Symmetries can be used for the determination of conservation currents [3], for the classification of differential equations [4][5][6][7][8][9][10] and for the reconnaissance of some well-known systems [11][12][13][14][15].In the recent literature, it has been shown that there is a close relation between the Lie symmetries of a second order differential equation and the geometry of the space where motion occurs. For example, the conservation of energy and angular momentum in Newtonian Physics is a result of the Lie point symmetries, generated by the Killing vectors of translations and rotations respectively.…”
mentioning
confidence: 99%
“…The reduction process is the main application of Lie symmetries, however, it is not a univocal approach. Symmetries can be used for the determination of conservation currents [3], for the classification of differential equations [4][5][6][7][8][9][10] and for the reconnaissance of some well-known systems [11][12][13][14][15].In the recent literature, it has been shown that there is a close relation between the Lie symmetries of a second order differential equation and the geometry of the space where motion occurs. For example, the conservation of energy and angular momentum in Newtonian Physics is a result of the Lie point symmetries, generated by the Killing vectors of translations and rotations respectively.…”
mentioning
confidence: 99%
“…. , 8 on the (t, x)-space are none other than the symmetries found in [13] for inhomogeneous and curved magnetic fields. Apart from v 0 , they constitute the symmetry generator (see equation (21)…”
Section: Equivalence Transformations In Terms Of Fieldsmentioning
confidence: 86%
“…and since the symmetries of the equivalence group are the only symmetries for inhomogeneous and curved magnetic fields it is of no surprise that they are none other than the ones found in [13] (see equations (26)-(27) therein) from the symmetry condition. Of course, the general solution to the above system for the electromagnetic potential was given there in terms of the symmetry generator.…”
Section: Classifying Equationsmentioning
confidence: 99%
“…where by substitute in (21) it follows Application of the differential invariants of the autonomous symmetry vector ∂ ξ in (23) lead to the nonlinear…”
Section: Travel-wave Solutionmentioning
confidence: 99%